Effects of hyaluronic acid on bone graft healing: An experimental study on sheep. - Muhmmed Ahmed Mustafa; Othman A. Omar (Erbil Dental Journal)
Background and Objectives: : Alloplastic is one of known materials have been used to treat bony defects in oral and maxillofacial region, but the healing is much more slower than auto graft . So many interpositional graft materials like hyaluronic acid and bone morphogenetic protein have been introduced to such material to induce osteoinductivity of graft material. This study aimed to evaluate the histological effect of Hyaluronic acid on bone graft substitute. Patients and methods: An experimental study carried out on 3 domestic sheep 2-4 years old. They divided into two groups, first group (study group): bone graft substitute mixed with hyaluronic acid introduced to the created cavities in the basal bone of mandible. Second group (control group): bone graft substitute were introduced into created cavities in the basal bone of mandible and the defects in both groups were covered with collagen membrane. The samples then sacrificed in deferent period interval 2 weeks, 6 weeks and 12 weeks and the sample collected and sent for histological examination. Results: all animals survived till the end of study. Both groups were characterized by new bone formation in defects however the bone formation in group 1 significantly preceded. Conclusion: hyaluronic acid induces the onset of Oral and Maxillofacial department.